Computer-aided design software for multi-stage amplifiers with bipolar transistors and field effect (2019)
The following article presents computer-aided design software for multi-stage amplifiers with bipolar transistors and field effect. It is composed of two units: a design and analysis unit that allows for step-by-step introduction of polarization and small signal values, the type of transistor to be used (bipolar or field effect) with their respective characterization values: current gain, thermal voltage, activation voltage, and saturation current, to result in the configurations and values of the resistors; and a theoretical unit that contains complete information on multi-stage amplifiers. A n-stage amplifier design method was developed, represented through a flowchart, and coded using a freely usable programming language. With the software, designs were made and simulated in a computational tool for academic use endorsed by the scientific community. The result for all variables evaluated was an average error of less than 2%. The research concludes that this software allows an effective design process of multi-stage amplifiers with bipolar transistors and field effect in a short time, it also allows changing the resistance values obtained for commercial values and calculating the error when implementing the circuit being a useful tool in the experimental area.